Day 1 Mon, November 09, 2020 2020
DOI: 10.2118/202742-ms
|View full text |Cite
|
Sign up to set email alerts
|

Smart Way for Consistent Cement Bond Evaluation and Reducing Human Bias Using Machine Learning

Abstract: Cement evaluation data acquired in oil and gas wells for confirmation of zonal isolation, channeling in cement behind casing and well integrity. All available technologies for cement evaluations are primarily measurements of acoustic parameters like amplitude of first arrival, full waveform recording of refracted wave, impedance and attenuation or there a combination. Generally, operationsPetrophysicist, petroleum engineer or service providers are responsible for evaluation of cement bond logs and propose reme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Viggen et al (2021) further improved this performance by reducing the negative combined effect of interpreter subjectivity and data complexity identified in their previous work by means of feature engineering (i.e., designing predictive features based on the raw log data) and using ML algorithms that are less susceptible to overfitting (Webb 2011). Voleti et al (2020) also reported good results with a comparable tool trained and tested on a small number of wells, estimating that it could save their company 75% of their current interpretation effort.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Viggen et al (2021) further improved this performance by reducing the negative combined effect of interpreter subjectivity and data complexity identified in their previous work by means of feature engineering (i.e., designing predictive features based on the raw log data) and using ML algorithms that are less susceptible to overfitting (Webb 2011). Voleti et al (2020) also reported good results with a comparable tool trained and tested on a small number of wells, estimating that it could save their company 75% of their current interpretation effort.…”
Section: Introductionmentioning
confidence: 95%
“…To help avoid getting many very short zones as seen in previous publications on automatic cement log interpretation tools (Reolon et al 2020, Viggen et al 2020, Voleti et al 2020, and Viggen et al 2021, the tool includes a post-processing component. The user can specify the minimum length of a zone (e.g., 3 m), and the tool will merge and/or replace shorter zones based on the classifier's class probability distribution.…”
Section: Interpretation Toolmentioning
confidence: 99%
“…In addition to this, there are other types. Deepak Kumar Voleti et al examined the efficacy of random forest classification and neural network models in cement evaluation and proposed the use of nested models that have low bias, improving interpretation accuracy and cement evaluation in onshore wells; however, the work did not address the issues of model generalizability, data dependency, or potential overfitting [15]. Ni Hongmei et al introduced a particle swarm optimization algorithm based on stochastic global optimization in neural network training.…”
Section: Relevant Workmentioning
confidence: 99%
“…Belozerov (2018) et al [7] used neural networks to identify reservoir locations from logging data, and Gkortsas (2019) et al [15] used support vector machines and neural networks to automatically identify ultrasonic waveform characteristics, which can predict additional information about the longitudinal wave velocity of annular materials in cased wells. Deepak Kumar Voleti et al [9] (2020) established different machine learning algorithms, such as random forest and neural network prediction based on CBL-VDL, and ultrasonic imaging data, to output the prediction results of cementing quality. Santos, L. et al [10] (2021) used the Gaussian process regression algorithm for training and generated new characteristic curves based on CBL and VDL logging data to accurately evaluate the cementing quality.…”
Section: Automatic Interpretation Based On Neural Networkmentioning
confidence: 99%
“…In 2015, Chen Xiangjun et al [8] proposed evaluating the cementing quality according to the method of acoustic energy, which has a high interpretation efficiency but insufficient accuracy. In 2020, Deepak Kumar Voleti et al [9] established different machine learning algorithms, such as CBL-VDL-based random forest and neural network prediction, and ultrasonic imaging data, to output the prediction results of cementing quality and achieve an automatic interpretation of cementing quality. In 2021, Santos, L. et al [10] used the Gaussian process regression algorithm for training, generated new characteristic curves according to CBL and VDL logging data, and accurately evaluated the cementing quality through the new curves.…”
Section: Introductionmentioning
confidence: 99%